(untitled) (Global Journal of Human-Social Science, 2017)
Health spending in the United States US has been steadily rising over the past several decades The Affordable Care Act ACA became law in 2010 but was not operational until 2014 The principal intention of the legislation was to provide insurance coverage to millions of US citizens who previously did not possess health insurance to improve Americans health In our study we compare the efficiency of health care resources on a state-by-state population basis in the US between the years of 2008-2015 Efficiencies are calculated using Data Envelopment Analysis DEA DEA can be defined as a non-parametric technique that uses linear programming lp to compare the relative efficiencies of homogenous Decision Making Units DMU in transforming inputs into outputs In this case the DMUs represent the states DEA uses lp models to build an efficiency frontier The efficiency frontier is determined by the most efficient states i e DMUs Therefore the efficiency of each state can be compared against the frontier and therefore against the most efficient ones